Financial Technology in Islamic View - Hidajat, Taofik (Universitas Muhammadiyah Sidoarjo, 2020)
The development of financial technology made many changes, including Islamic finance. This paper reviews how fintech is changing the shape of the Islamic finance industry through mobile payments, microfinance, peer-to-peer lending, and crowdfunding. The use of e-wallet is as long as it does not violate the provisions. Microfinance cannot be separated from Islamic finance if we want to increase social welfare through inclusive growth and encourage the distribution of wealth. Islamic microfinance structure can deal with the problem of poverty. The appropriate and fair crowdfunding model for small businesses is profit sharing or using mudaraba contracts. In Islamic finance, the role of bitcoin is controversial.